Trans-ultra wide band gap perovskite solar cell and preparation method and application thereof

By adding polyhexamethyleneguanidine hydrochloride (PHMG) to the perovskite precursor of perovskite solar cells, the problem of open circuit voltage loss at high Br content is solved, and the battery is efficient, stable and suitable for low-light environments is achieved.

CN119584824APending Publication Date: 2025-03-07YUNNAN UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411485818.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Ultra-wide bandgap perovskite solar cells are prone to photogenerated phase separation and non-radiative recombination under high Br content, resulting in large open circuit voltage loss, affecting the long-term operation stability of the device and commercial application prospects.

Method used

Polyhexamethyleneguanidine hydrochloride (PHMG) is added to the perovskite precursor of perovskite solar cells to delay the crystallization rate of thin films, reduce surface interface defects, and improve the open circuit voltage, efficiency and stability of the battery.

Benefits of technology

By adding PHMG, the open circuit voltage, efficiency and stability of perovskite solar cells are significantly improved, suitable for low-light environments, and have excellent commercial prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119584824A_ABST
    Figure CN119584824A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solar cells, in particular to a trans-ultra-wide-band-gap perovskite solar cell and a preparation method and application of the trans-ultra-wide-band-gap perovskite solar cell. Comprising the following steps: (1) cleaning a conductive glass substrate; (2) depositing a hole transport layer on the conductive glass substrate; (3) adding polyhexamethylene guanidine hydrochloride into a perovskite precursor solution, and depositing the perovskite precursor solution on the hole transport layer to obtain a perovskite light absorption layer; (4) depositing an electron transport layer and a buffer layer on the perovskite light absorption layer; and (5) depositing a metal electrode on the buffer layer. The polyhexamethylene guanidine hydrochloride (PHMG) is added into the perovskite precursor of the perovskite solar cell, so that the crystallization rate of a thin film is delayed, surface and interface defects are reduced, and the open-circuit voltage, the efficiency and the stability of the cell are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells, and in particular to an inverted ultra-wide bandgap perovskite solar cell and a preparation method and application thereof. Background Art

[0002] Tandem solar cells based on perovskite materials can surpass the theoretical efficiency limit in existing photovoltaic technology. The current record of power conversion efficiency (PCE) of perovskite tandem is 34.6%. The excellent photovoltaic properties have attracted the attention of many researchers. Ultra-wide bandgap (UWBG) perovskites with a bandgap exceeding 1.90eV are suitable for triple-junction all-perovskite tandem solar cells (TJSC) and indoor photovoltaic applications, providing an effective way to further improve efficiency. The Br content in ultra-wide bandgap perovskite materials often exceeds 20%, and photoinduced phase separation and non-radiative recombination are prone to occur, resulting in large open-circuit voltage loss of the device, affecting long-term operating stability and commercial application prospects.

[0003] In ultra-wide bandgap inverse perovskite solar cells, many researchers have adjusted the composition and reduced the opening voltage loss by directly replacing Br with chloride anions or halide-like thiocyanates. - When the content reaches a certain level, the solubility will deteriorate and some Cl elements will volatilize during the thermal annealing process of the film, which will not affect the final perovskite battery device. - ) will affect the crystallization process of the perovskite film and increase the open circuit voltage. In addition, single anion doping cannot improve the open circuit voltage in all aspects. Summary of the invention

[0004] In order to solve the defects in the prior art, the present invention provides an inverted ultra-wide bandgap perovskite solar cell and a preparation method and application thereof. The present invention adds polyhexamethyleneguanidine hydrochloride (PHMG) to the perovskite precursor of the perovskite solar cell to slow down the crystallization rate of the film, reduce surface and interface defects, and improve the open circuit voltage, efficiency and stability of the cell.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing an inverse ultra-wide bandgap perovskite solar cell, comprising the following steps:

[0007] (1) Clean the conductive glass substrate;

[0008] (2) depositing a hole transport layer on the conductive glass substrate;

[0009] (3) adding polyhexamethyleneguanidine hydrochloride to the perovskite precursor solution and depositing it on the hole transport layer to obtain a perovskite light absorbing layer;

[0010] (4) depositing an electron transport layer and a buffer layer on the perovskite light absorbing layer;

[0011] (5) Depositing a metal electrode on the buffer layer.

[0012] Preferably, the amount of polyhexamethyleneguanidine hydrochloride added is 1 to 4 mg / ml. Exemplarily, the amount of polyhexamethyleneguanidine hydrochloride added is any one of 1 mg / ml, 2 mg / ml, 3 mg / ml, 4 mg / ml, or a value therebetween. More preferably, the amount of polyhexamethyleneguanidine hydrochloride added is 1 mg / ml.

[0013] Preferably, the deposition in step (3) is spin coating, and the spin coating adopts two-step spin coating, and the two-step speed parameters are respectively 1000 rpm for 10 seconds, an acceleration of 1000 rpm / s, and 5000 rpm for 30 seconds, an acceleration of 2000 rpm / s.

[0014] Preferably, the annealing conditions during deposition in step (3) are 100° C. for 12 min.

[0015] Preferably, the material of the hole transport layer is selected from any one or more of MeO-2PACz, 4PADBCz, and 4PACz.

[0016] Preferably, the perovskite precursor solution is prepared using CsI, FAI, PbI2, and PbBr2 as raw materials.

[0017] Preferably, the material of the electron transport layer is PCBM or C 60 .

[0018] Preferably, the material of the buffer layer is BCP.

[0019] Preferably, the metal electrode material is selected from any one of Ag, Au or Cu.

[0020] In a second aspect, the present invention provides an inverted ultra-wide bandgap perovskite solar cell prepared by the above preparation method.

[0021] In a third aspect, the present invention provides an application of a solar cell in a weak light environment, wherein the solar cell is the above-mentioned inverted ultra-wide bandgap perovskite solar cell, and the weak light condition is an irradiation intensity of 147 to 228 W / m 2 .

[0022] The beneficial effects of the present invention are:

[0023] In the process of preparing an inverse ultra-wide bandgap perovskite solar cell, polyhexamethylene guanidine hydrochloride (PHMG) is added to a perovskite precursor when preparing a perovskite light-absorbing layer. The guanidine (GA) cation and a long carbon chain structure mainly play the following roles: (1) The guanidine (GA) cation has a large radius and can partially enter the perovskite lattice structure, thereby improving the stability of the perovskite structure and coordinating with uncoordinated Pb 2+ (1) The molecular formula contains a long chain structure with a certain hydrophobicity, which can improve the humidity stability of the perovskite film; (2) The molecular formula contains a long chain structure with a certain hydrophobicity, which can improve the humidity stability of the perovskite film; (3) The perovskite film is optimized for crystallization by forming hydrogen bonds through multiple sites, inhibiting FA + (4) The synergistic effect of ions makes the battery device more reproducible and more suitable for all-perovskite stacking and indoor photovoltaic applications.

[0024] The inverted ultra-wide bandgap perovskite solar cell obtained by the preparation method of the present invention has good film crystallization quality, high flatness, excellent electrochemical performance, long-term thermal stability and humidity stability, is suitable for weak light environments, and has excellent commercial prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 XRD diagrams of the perovskite films of the embodiments and comparative examples;

[0026] Figure 2 The SEM images of the perovskite films of Example 1 and Comparative Example 1;

[0027] Figure 3 It is a box diagram of battery efficiency of the embodiment and the comparative example;

[0028] Figure 4 Statistical distribution histogram of open circuit voltage of batteries in Example 1 and Comparative Example 1;

[0029] Figure 5 It is the thermal stability test diagram of Example 1 and Comparative Example 1;

[0030] Figure 6 This is a humidity stability test diagram of the perovskite film prepared in Example 1 and Comparative Example 1;

[0031] Figure 7 This is a JV curve diagram of the solar cell prepared in Example 1 under weak light environment. DETAILED DESCRIPTION

[0032] In order to enable those skilled in the art to better understand the technical solution of the invention, the present invention is further described in detail below in conjunction with specific implementation methods.

[0033] Example 1

[0034] This embodiment provides an inverted ultra-wide bandgap perovskite solar cell, whose structure includes, from bottom to top, conductive glass, a hole transport layer, a perovskite light absorption layer, an electron transport layer, a buffer layer, and a metal electrode.

[0035] The method for preparing the inverse ultra-wide bandgap perovskite solar cell comprises the following steps:

[0036] (1) Cleaning of conductive glass: The indium tin oxide (ITO) conductive glass substrate was gently wiped clean with anhydrous ethanol, and then treated in a UV light and ozone cleaning machine for 20 minutes to remove impurities on the substrate surface and improve the substrate wettability;

[0037] (2) Preparation of hole transport layer: 70 μL of 0.6 mg / ml dimethoxycarbazole (Me-2PACz) solution (solvent: ethanol) was spin-coated on a conductive glass substrate at a speed of 3000 rpm for 30 s and an acceleration of 3000 rpm / s. To ensure uniformity of the film, the solution was allowed to stand for 5 s before spin coating. The film was then placed on a hot plate at 100°C for 10 min for thermal annealing to obtain a hole transport layer.

[0038] (3) Preparation of perovskite light absorbing layer: The precursor solution was prepared by dissolving 38.95 mg of cesium iodide (CsI), 146.2 mg of formamidine hydroiodide (FAI), 46.1 mg of lead iodide (PbI2) and 330.3 mg of lead bromide (PbBr2) in 1 mL of DFM:DMSO (volume ratio of 4:1) solvent and stirring for 1 hour to fully dissolve. Then, PHMG (weight average molecular weight of 171.283 g / mol) was added at a ratio of 1 mg / ml and mixed well. The film was spin-coated on the hole transport layer in two steps, with a spin coating amount of 50 μl, and the two-step speed parameters were 1000 rpm for 10 s, an acceleration of 1000 rpm / s, and 5000 rpm for 30 s, an acceleration of 2000 rpm / s, and 150 μl of anisole was added as an anti-solvent in the last 10 s of the spin coating time to promote the crystallization of the perovskite film. Finally, the film after spin coating was placed on a hot plate at 100°C for thermal annealing for 12 min to obtain a perovskite light absorbing layer.

[0039] (4) Preparation of electron transport layer and buffer layer: First, spin-coat phenyl-C with a concentration of 20 mg / ml on the perovskite light absorption layer. 61 -Methyl butyrate (PC 61BM) (the solvent is chlorobenzene) 40 μl, the spin coating speed is 1500 rpm for 30 s, the acceleration is 1500 rpm / s, as an electron transport layer; then spin coating 0.5 mg / ml bathocuproine (BCP) (the solvent is isopropanol) 60 μl, the spin coating speed is 6000 rpm, 30 s, the acceleration is 6000 rpm / s, as a buffer layer;

[0040] (5) Preparation of metal electrode: Ag electrode was deposited onto the BCP buffer layer by thermal evaporation method to serve as electrode with a thickness of 120 nm.

[0041] The band gap of the inverse perovskite solar cell prepared in Example 1 is 1.93 eV.

[0042] Example 2

[0043] Same as Example 1, except that the amount of PHMG added is 2 mg / ml.

[0044] The band gap of the inverse perovskite solar cell prepared in Example 2 is 1.93 eV.

[0045] Example 3

[0046] Same as Example 1, except that the amount of PHMG added is 3 mg / ml.

[0047] The band gap of the inverse perovskite solar cell prepared in Example 3 is 1.93 eV.

[0048] Example 4

[0049] Same as Example 1, except that the amount of PHMG added is 4 mg / ml.

[0050] The band gap of the inverse perovskite solar cell prepared in Example 4 is 1.93 eV.

[0051] Comparative Example 1

[0052] The same as Example 1, except that PHMG was not added during the preparation process of step (3).

[0053] The band gap of the inverse perovskite solar cell prepared in Comparative Example 1 is 1.93 eV.

[0054] Effect Example 1 Crystal Quality Characterization

[0055] The present invention uses an X-ray diffraction analyzer (XRD) to characterize the crystalline quality of the perovskite films obtained in the embodiments and comparative examples. The results are shown in Figure 1The diffraction peaks at 14.52° and 29.28° correspond to the characteristic diffraction peaks of the (110) and (220) crystal planes of the perovskite crystal, respectively. It can be seen that compared with Comparative Example 1, the diffraction peak intensity of the films doped with PHMG in Examples 1 to 5 increases, among which the diffraction intensity of the characteristic peak of Example 1 is the strongest, indicating that the crystal quality of the film is the best at this PHMG concentration. In addition, after the introduction of PHMG, the (110) crystal plane diffraction peak slightly moves to a smaller angle, indicating that the GA with a larger ionic radius + It can successfully enter the perovskite lattice and promote the stability of the lattice structure.

[0056] Effect Example 2 Surface morphology characterization

[0057] The present invention uses thermal field emission scanning electron microscopy (SEM) to characterize the surface morphology of the perovskite film obtained in Example 1 and Comparative Example 1. The results are shown in Figure 2 The SEM images show that the film of Comparative Example 1 has obvious cracks at the grain boundaries and the grain surface is uneven, while the uniform flatness of the grains of the film obtained in Example 1 is significantly improved, and the grain size is more uniform and dense, indicating that PHMG has a positive effect on reducing film defects and crystallization dynamics, and improves the film morphology.

[0058] Effect Example 3 Performance Measurement of Solar Cells

[0059] According to the methods of Examples 1 to 4 and Comparative Example 1, 20 groups of battery devices were prepared respectively to measure the battery efficiency. The results are shown in Figure 3 .from Figure 3 It can be seen from the box diagram that the efficiency of the battery devices obtained in Comparative Example 1 is less than 15%. After the introduction of PHMG in Examples 1 to 3, the battery efficiency is improved to a certain extent, among which the device obtained in Example 1 has the best performance, all of which are above 16%, indicating that the perovskite solar cell prepared by introducing PHMG has reliability, reproducibility and high photovoltaic performance.

[0060] To further verify that PHMG can improve the open circuit voltage of the device, 30 groups of battery devices were prepared according to the methods of Example 1 and Comparative Example 1 to measure the open circuit voltage. Figure 4 The open circuit voltage statistical distribution histogram shows that Example 1 of the additive PHMG can increase V OC It was increased from the original 1.35V to 1.43V, effectively reducing the open-circuit voltage loss, proving that the device has good repeatability and high open-circuit voltage.

[0061] In order to explore the thermal stability of the solar cell prepared in the embodiment of the present invention, the battery devices prepared in Example 1 and Comparative Example 1 were placed in a nitrogen (N2) glove box and heated at 60°C to explore their thermal stability. Figure 5.from Figure 5 It can be seen from the thermal stability efficiency diagram that the battery device prepared in Example 1 still maintains 80% of the initial efficiency after 60 days, while the battery device performance obtained in Comparative Example 1 only maintains 60% of the initial efficiency after 40 days of continuous heating, which further confirms that PHMG as an additive can improve the thermal stability of perovskite solar cell devices.

[0062] In order to explore the effect of PHMG on the humidity stability of perovskite films, the perovskite films prepared in Example 1 and Comparative Example 1 were placed in air at a temperature of 23±2°C and a relative humidity of 46%±2 for humidity stability testing. The results are shown in Figure 6 The surface of the perovskite film obtained in Comparative Example 1 had decomposed after being placed for 60 days, while the perovskite film obtained in Example 1 after being treated with PHMG did not show obvious decomposition, which confirmed that the long chain structure contained in the PHMG molecule was hydrophobic, so that the humidity stability of the film was improved.

[0063] Effect Example 4: Application in low light environment

[0064] The present invention is a trans-one-step ultra-wide bandgap (1.93 eV) perovskite solar cell, which mainly uses PHMG to increase the open circuit voltage and reduce the open voltage loss, while not changing the bandgap, making the bandgap suitable for use in weak light environments and making full use of the light source. To verify this effect, the solar cell device obtained in Example 1 of the present invention was subjected to a simulated underwater illumination JV test.

[0065] Experimental conditions: carried out in a nitrogen-filled glove box at a temperature of 23°C, using a xenon lamp as the light source, and the radiometer showed an intensity of 228W / m at a water depth of 10 meters. 2 ; When the depth reaches 30 meters, the radiometer shows an intensity of 147W / m 2 .

[0066] Test 228W / m 2 and 147W / m 2 Electrochemical performance of solar cells under irradiation intensity. The results are shown in Figure 7 and Table 1.

[0067] Table 1

[0068] water depth Irradiation intensity <![CDATA[V OC (V)]]> <![CDATA[J SC (mA / cm 2 )]]> FF(%) PCE(%) 10 meters <![CDATA[228W / m 2 ]]> 1.36 9.13 76.08 9.46 30 meters <![CDATA[147W / m 2 ]]> 1.34 5.12 77.25 5.31

[0069] Figure 7 The JV curves of the solar cell prepared in Example 1 under weak light environment correspond to the water depth of 10 meters and 30 meters respectively. The deeper the water, the weaker the light intensity. The specific photovoltaic parameters of the device are shown in Table 1. It can be seen that no matter what kind of weak light environment, the open circuit voltage (V OC) and fill factor (FF) did not change significantly, but the current increased from 5.12 mA / cm in the 30 m environment. 2 Improved to 9.13mA / cm at 10 meters 2 Similarly, the photovoltaic conversion efficiency (PCE) increased from 5.31% to 9.46%. This proves that the open circuit voltage of the battery device doped with PHMG is stable and suitable for application in weak light environment.

[0070] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing an inverse ultra-wide bandgap perovskite solar cell, characterized in that: The following steps are involved: (1) Clean the conductive glass substrate; (2) depositing a hole transport layer on the conductive glass substrate; (3) adding polyhexamethyleneguanidine hydrochloride to the perovskite precursor solution and depositing it on the hole transport layer to obtain a perovskite light absorbing layer; (4) depositing an electron transport layer and a buffer layer on the perovskite light absorbing layer; (5) Depositing a metal electrode on the buffer layer.

2. The preparation method according to claim 1, characterized in that: The added amount of the polyhexamethyleneguanidine hydrochloride is 1-4 mg / L.

3. The preparation method according to claim 1, characterized in that: The deposition in step (3) is spin coating, and the spin coating adopts two-step spin coating, and the rotation speed parameters of the two steps are respectively 1000 rpm for 10 seconds, an acceleration of 1000 rpm / s, and 5000 rpm for 30 seconds, an acceleration of 2000 rpm / s.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The material of the hole transport layer is selected from any one or more of MeO-2PACz, 4PADBCz, and 4PACz.

5. The preparation method according to any one of claims 1 to 3, characterized in that: The perovskite precursor solution is prepared from CsI, FAI, PbI2 and PbBr2 as raw materials.

6. The preparation method according to any one of claims 1 to 3, characterized in that: The material of the electron transport layer is PCBM or C 60 .

7. The preparation method according to any one of claims 1 to 3, characterized in that: The material of the buffer layer is BCP.

8. The preparation method according to any one of claims 1 to 3, characterized in that: The metal electrode material is selected from any one of Ag, Au or Cu.

9. An inverse ultra-wide bandgap perovskite solar cell prepared by the preparation method according to any one of claims 1 to 8.

10. An application of a solar cell in a weak light environment, characterized in that: The solar cell is the inverted ultra-wide bandgap perovskite solar cell according to claim 9, and the weak light condition is an irradiation intensity of 147 to 228 W / m 2 .

Citation Information

Patent Citations

  • Preparation method of perovskite device

    CN115884645A

  • Guanidine salt modified trans-perovskite solar cell and preparation method thereof

    CN117881259A